2016
DOI: 10.18632/oncotarget.13919
|View full text |Cite
|
Sign up to set email alerts
|

Overactive mTOR signaling leads to endometrial hyperplasia in aged women and mice

Abstract: During aging, uncontrolled epithelial cell proliferation in the uterus results in endometrial hyperplasia and/or cancer development. The mTOR signaling pathway is one of the major regulators of aging as suppression of this pathway prolongs lifespan in model organisms. Genetic alterations in this pathway via mutations and/or amplifications are often encountered in endometrial cancers. However, the exact contribution of mTOR signaling and uterine aging to endometrial pathologies is currently unclear. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
1
29
0
1
Order By: Relevance
“…Multivariate analysis showed that the mTOR inhibitor reduced the risk of malignancy by 60% and the risk of solid malignancy by 55%. 28 Additionally, in a study by Bajwa et al, 29 they showed that overactivation of mTOR signaling causes endometrial hyperplasia, and using rapamycin as In conclusion, we are of the opinion that precancerous pathologies of the endometrium, such as hyperplasia, in renal transplant patients are increased by an increased estrogenic effect due to immunosuppressive agents used to prolong the survival of transplant patients and impaired hormone metabolism. Therefore, regular oncological screening should be performed in these patients, and early treatment of precancerous conditions should be administered.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Multivariate analysis showed that the mTOR inhibitor reduced the risk of malignancy by 60% and the risk of solid malignancy by 55%. 28 Additionally, in a study by Bajwa et al, 29 they showed that overactivation of mTOR signaling causes endometrial hyperplasia, and using rapamycin as In conclusion, we are of the opinion that precancerous pathologies of the endometrium, such as hyperplasia, in renal transplant patients are increased by an increased estrogenic effect due to immunosuppressive agents used to prolong the survival of transplant patients and impaired hormone metabolism. Therefore, regular oncological screening should be performed in these patients, and early treatment of precancerous conditions should be administered.…”
Section: Discussionmentioning
confidence: 91%
“…They showed that the overall incidence of malignancy was 0.6% in both the sirolimus/everolimus alone group and the sirolimus or everolimus with a cyclosporin group, and 1.81% in the cyclosporine group (P < .0001) 28. Additionally, in a study by Bajwa et al,29 they showed that overactivation of mTOR signaling causes endometrial hyperplasia, and using rapamycin as an mTOR signaling inhibitor suppressed endometrial hyperplasia in aged mice. Multivariate analysis showed that the mTOR inhibitor reduced the risk of malignancy by 60% and the risk of solid malignancy by 55% 28.…”
mentioning
confidence: 97%
“…The majority of endometrial cancers harbor alterations in the PI3K‐mTOR pathway and are driven by estrogen . To determine the feasibility of using our endometrial cancer co‐culture spheroid model for drug screening, we tested the responsiveness of these spheroids with two well‐known gynecological cancer drugs, tamoxifen and everolimus.…”
Section: Resultsmentioning
confidence: 99%
“…Etiological processes underlying many gynecological conditions have not yet been completely identified. The Pi3k/Akt1/mTor and p53 signaling pathways appear to be involved in the pathophysiological mechanisms of gynecopathies including polycystic ovarian syndrome, premature ovarian failure, leiomyoma, endometriosis, and gynecological cancers [8][9][10][11][12][13][14][15]. This signaling pathway has also been implicated in fibrosis in different tissues, such as the kidney, lung, and liver [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%